2019
DOI: 10.7759/cureus.3962
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cholangiocarcinoma in the USA from 2001 to 2015: A US Cancer Statistics Analysis of 50 States

Abstract: IntroductionCholangiocarcinoma is an aggressive and rare cancer of the bile duct with a very poor prognosis. It accounts for approximately three percent of gastrointestinal cancers but nearly 20 percent of deaths are from hepatobiliary cancers. Cholangiocarcinoma is also a clinically silent disease that presents at advanced stages. In this study, we wanted to identify subpopulations at the greatest risk of developing cholangiocarcinoma such that we can improve diagnosis and ultimately reduce the cancer mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 11 publications
1
69
0
2
Order By: Relevance
“…Six (four high and two moderate quality) of the eight included studies reported increasing trends, and two (both moderate quality) found decreasing trends (Figure 2, Table 1, Supplementary Table 3.4). All three studies from the USA (64)(65)(66) and one from the Netherlands (70) described increasing short-or long-term trends among persons over recent decades until at least the late 2000s. While sex-specific rates increased from 1999 to 2005 (68) in South Korea, another study from the same country reported decreasing trends among persons over the decade until 2015 (67).…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…Six (four high and two moderate quality) of the eight included studies reported increasing trends, and two (both moderate quality) found decreasing trends (Figure 2, Table 1, Supplementary Table 3.4). All three studies from the USA (64)(65)(66) and one from the Netherlands (70) described increasing short-or long-term trends among persons over recent decades until at least the late 2000s. While sex-specific rates increased from 1999 to 2005 (68) in South Korea, another study from the same country reported decreasing trends among persons over the decade until 2015 (67).…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…1 Its incidence however, has seen an increase in the past decade. 2,3 The disease is considered incurable unless complete resection is possible; however, only 15% of the tumors are operable. 4 In such cases, chemotherapy and radiation therapy (RT), particularly stereotactic body radiotherapy (SBRT) and hypofractionated RT, are used to extend survival and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, approximately 3000 new cases of BTC are diagnosed each year. BTC represent 0.8% of all tumors in males and 1.6% of all tumors in females [3]. However, the incidence of BTC is rising.…”
Section: Introductionmentioning
confidence: 99%